Efektifitas Pemberian Serbuk Jahe (Zingiber Officinale) Terhadap Tingkatan Mual Muntah Pada Ibu Hamil - Finta Isti Kundarti; Dwi Estuning Rahayu; Reni Utami (Akademi Keperawatan Dharma Husada Kediri, 2015)
Nausea and vomiting is a common disorder experienced by 50% of pregnant women in the first trimester of pregnancy. Efforts to reduce the symptoms can be with food or drinks containing ginger. Ginger has antiemetic and anxiolytic activity. The aim of this study was to determine the effectiveness of ginger to decrease nausea and vomiting in pregnant women 0-16 weeks gestation. The type of research design used is quasy Experimental design. The population in this study were all pregnant women 0-16 weeks gestation who experience nausea and vomiting as many as 24 people in the sub-district Puskesmas Wonorejo Ngadiluwih Kediri. The sample in this study 24 people with using cluster random sampling and systematic sampling. The instrument used was a questionnaire and rhodes INVR. Analysis of the results using Wilcoxon Match Pairs Test test results obtained p value 0.033 <0.05 then H0 is rejected so that there are differences decrease nausea and vomiting in pregnant women 0-16 weeks gestation who were not given the ginger and ginger. In conclusion the effective administration of ginger powder to decrease nausea and vomiting in pregnant women aged 0-16 weeks. Suggested for health workers to use ginger as a treatment alternative for reducing nausea and vomiting inpregnant women.Keywords: Giving of ginger powder, decrease of nausea and vomiting, pregnant women